2019
DOI: 10.1111/ijfs.14247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food ingredients on glucagon‐like peptide‐1 secretion in STC‐1 and HuTu‐80 cells

Abstract: Summary This study aims at identifying food ingredients that have potential to enhance satiety and therefore potentially can be used for preventing and treating obesity. To do so, effects of thirteen food ingredients on the secretion of gut satiety hormone glucagon‐like peptide‐1 (GLP‐1) in enteroendocrine STC‐1 and HuTu‐80 cells were investigated. First, the effects of food ingredients on cell viability were investigated. This was done to determine if the individual ingredient affected cell viability, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Especially, a synergistic effect has been observed by certain AAs to result in a potent stimulation of the β-cells [45,47]. Leucine, in particular, seems to be the potent stimulator of insulin secretion [8,45,48]. A study by Upshaw et al [29] reported no effect in same-day-TT performance, when investigating the effect of different protein types, including animal-and plant-based proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, a synergistic effect has been observed by certain AAs to result in a potent stimulation of the β-cells [45,47]. Leucine, in particular, seems to be the potent stimulator of insulin secretion [8,45,48]. A study by Upshaw et al [29] reported no effect in same-day-TT performance, when investigating the effect of different protein types, including animal-and plant-based proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that methodological differences exist across trials to a great extent, which could explain the differences in performance outcome in the literature. Considering that the digestive properties and AA profile of proteins may differentially affect muscle protein synthesis and glycogen synthesis (by mediating insulin-secretion) [8,45,46,48], future research should assess whether manipulating the source of protein (e.g., animal-or plant-based) exerts enhanced effect on performance. Furthermore, more studies investigating long-term recovery, assessing muscle glycogen levels through biopsy techniques, as well as the timing of CHO-PRO intake (e.g., during exercise and/or recovery) are warranted.…”
Section: Future Researchmentioning
confidence: 99%
“…Interestingly, there is a paucity of data regarding the biological role of plant‐based milk substitutes, especially their satiating properties. Nevertheless, recent studies exhibited that polyphenol‐rich foods such as green tea, curcumin (Planes‐Munoz et al., 2018), and other plant epigallocatechin‐gallate, hesperetin, rosemary extract, and kale extract (Yue et al., 2019) can suppress the appetite and control food intake. The current data are in line with these previously reported data, proposing that these milk alternatives could participate in appetite suppression through GLP‐1 and CCK secretion.…”
Section: Resultsmentioning
confidence: 99%
“…This is not supported by our studies on isolated perfused rat small intestine, where intra-luminal or intra-arterial RE infusion did not stimulate the secretion of intestinal GLP-1. However, our previous in vitro studies showed augmented secretion of GLP-1 from STC-1 and HuTu-80 cells when stimulated with RE [ 12 ]. The discrepancy between the long-term and acute effects of RE on GLP-1 secretion points towards an adaptive effect of RE, as previously seen for nutritional modulation of GLP-1 secretion [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro studies showed that rosemary extract (RE) stimulated the secretion of the satiety-inducing hormone Glucagon-like peptide-1 (GLP-1) from immortalized GLP-1 producing cell lines [ 12 ]. GLP-1 is a peptide hormone secreted from intestinal L-cells in response to nutrients in the intestinal lumen.…”
Section: Introductionmentioning
confidence: 99%